2013
DOI: 10.1155/2013/463740
|View full text |Cite
|
Sign up to set email alerts
|

Both ERK/MAPK and TGF-Beta/Smad Signaling Pathways Play a Role in the Kidney Fibrosis of Diabetic Mice Accelerated by Blood Glucose Fluctuation

Abstract: Background. The notion that diabetic nephropathy is the leading cause of renal fibrosis prompted us to investigate the effects of blood glucose fluctuation (BGF) under high glucose condition on kidney in the mice. Methods. The diabetic and BGF animal models were established in this study. Immunohistochemistry, Western blot, and RT-PCR analysis were applied to detect the expression of type I collagen, matrix metalloproteinase-1 (MMP1), metalloproteinase inhibitor 1 (TIMP1), transforming growth factor beta 1 (TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 26 publications
3
73
0
Order By: Relevance
“…Hyperglycaemia leads to activation (phosphorylation) of mitogen-activated protein kinases (MAPKs) p38, JNK and ERK1/2, hypertrophy and fibrosis in the heart [32][33][34][35][36][37][38] and kidney [39,40]. While little evidence is available to suggest strong tissue specific activation of proinflammatory pathways in STZ-induced diabetes, pharmacological inhibition or genetic deletion of any of these three MAPKs reduces microvascular complications (diabetic nephropathy, cardiomyopathy and retinopathy) caused by type 1 diabetes in rodents [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia leads to activation (phosphorylation) of mitogen-activated protein kinases (MAPKs) p38, JNK and ERK1/2, hypertrophy and fibrosis in the heart [32][33][34][35][36][37][38] and kidney [39,40]. While little evidence is available to suggest strong tissue specific activation of proinflammatory pathways in STZ-induced diabetes, pharmacological inhibition or genetic deletion of any of these three MAPKs reduces microvascular complications (diabetic nephropathy, cardiomyopathy and retinopathy) caused by type 1 diabetes in rodents [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…However, CTGF may play an important role in renal fibrosis independent of TGF-β [23]. For example, CTGF can bind to low-density lipoprotein receptor-related protein (LRP1) and epidermal growth factor receptor (EGFR) to activate profibrotic ERK signalling in the kidney [33, 34]. Moreover, many studies have demonstrated that directly decreasing CTGF expression effectively modulates kidney disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our PCR results showed that EGCG inhibited the transcription of Smad3 mRNA ERK is a serine/threonine protein kinase that belongs to the mitogen-activated protein kinase (MAPK) family. Pi-ERK expression was found to be elevated in a variety of pulmonary fibrosis and liver fibrosis models, indicating that the ERK pathway is involved in the occurrence of fibrotic lesions to some extent (Robledo et al, 2000;Fubini and Hubbard, 2003;Kim et al, 2007;Cheng et al, 2013). TGF-b1-induced fibrosis regulation was achieved by acetylation of Smad3 (Kim et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%